Angiotensin Converting Enzyme Inhibitors and Alzheimer Disease in the Presence of the Apolipoprotein E4 Allele - Qiu, Wendy Wei Qiao (2013)
OBJECTIVE: The effect of angiotensin converting enzyme (ACE) inhibitors on Alzheimer disease (AD) remains unclear, with conflicting results reported. We studied the interaction of the Apolipoprotein E (ApoE) genotype and ACE inhibitors on AD. METHODS: This was a cross-sectional study of homebound elderly with an AD diagnosis and documentation of medications taken. ApoE genotype was determined. RESULTS: A total of 355 subjects with status on ApoE alleles and cognitive diagnoses were studied. The average age (mean ± SD) of this population was 73.3 ± 8.3 years old, and 73% were female. Cross-sectionally, there was no difference in the number of AD cases between ApoE4 carriers and ApoE4 non-carriers or between ACE inhibitor users and non-users in the homebound elderly. ApoE4 carriers treated with ACE inhibitors, however, had more diagnoses of AD compared with those who did not have the treatment (28% versus 6%, p = 0.01) or ApoE4 non-carriers treated with an ACE inhibitor (28% versus 10%, p = 0.03). ACE inhibitor use was associated with AD diagnosis only in the presence of an E4 allele. Using multivariate logistic regression analysis, we found that in diagnosed AD cases there was a significant interaction between ApoE4 and ACE inhibitor use (odds ratio: 20.85; 95% confidence interval: 3.08–140.95; p = 0.002) after adjusting for age, sex, ethnicity, and education. CONCLUSION: The effects of ACE inhibitors on AD may be different depending on ApoE genotype. A prospective study is needed to determine whether ACE inhibitor use accelerates or poorly delays AD development in ApoE4 carriers compared with ApoE4 non-carriers.